Genetic variability in geographical populations of Aedes aegypti (Diptera, Culicidae) in Brazil elucidated by molecular markers - Paduan, Karina dos Santos [UNESP]; Araújo-Júnior, João P. [UNESP]; Ribolla, Paulo E.M. [UNESP] (Sociedade Brasileira de Genética, 2006)
The tropical mosquito, Aedes aegypti is the most important domestic vector of urban yellow fever and dengue. Genetic population studies on this vector are important because they may lead to new tools for surveillance. An analysis of genetic structure was conducted among populations of A. aegypti from 11 localities in four demographic regions within six Brazilian federal states. Markers included 21 random amplified polymorphic DNA (RAPD) loci. RAPD markers were detected among populations and cluster analysis revealed two main groups. We found high genetic polymorphism (H S = 0.224) and high levels of genetic differentiation between populations from different states (G ST = 0.430), as well as in populations from cities in the same state (G ST = 0.410). These results indicate significant differentiation in A. aegypti populations in Brazil. Regression analyses of geographic distances and pairwise F ST values estimated from RAPD markers showed that there is a correlation between genetic structure and geographic localization.
Keywords: Aedes aegypti; population genetics; random amplified polymorphic DNA; genetic variability